Luminol - Lewis, Simon (John Wiley and Sons Inc, 2009)
Ever since its forensic potential was first reported in 1928 [1], luminol (5-amino-2,3-dihydro-1,4-phthalazinedione or 3-aminophthalhydrazide, Figure 1) has been utilized for the detection of latent bloodstains during investigations involving violent crime. This use is based upon the emission of light when a reagent containing luminol and hydrogen peroxide is applied to the suspect stain, the resulting glow being due to the reaction of luminol with hemoglobin. The key events in the discovery, study, and use of luminol as a forensic reagent are presented in Figure 2. Despite the age of this presumptive test, there is still significant interest in the forensic community due to its high sensitivity and lack of damage on genetic material, allowing subsequent DNA analysis (see DNA). This interest has resulted in a number of recent publications, including modifications to the technique, a new, commercially available formulation, and studies on its performance as a forensic test. Recently, the authors carried out a comprehensive review of the forensic application of the luminol reaction as a presumptive test forlatent blood detection, upon which this article is substantially based.